Faktor-Faktor Yang Mempengaruhi Pendapatan Kerajinan Anyaman Purun (Studi Kasus: Kelompok Pengrajin Kerajinan Anyaman Purun Al-Firdaus di Kampung Purun, Kelurahan Palam, Kota Banjarbaru) - Aulia, Redhana; Hafizah, Hafizah; Almaisarah, Almaisarah (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2024)
Purun woven crafts are an important economic activity for the people of Purun Village, Palam Village, Banjarbaru City. This study aims to identify factors that influence the income of Purun woven crafts in the context of the Purun Al-Firdaus Woven Crafts Craftsmen Group. The respondents in this study were members of the Purun Al-Firdaus Woven Crafts Craftsman Group who were actively involved in the production and marketing of Purun woven crafts as many as 45 people. The research results show that there are several factors that influence income from purun woven crafts. These factors include: production amount, craftsmen's wages, work experience, and working hours. The results of the research show that the amount of production and craftsmen's wages have a significant effect, while work experience and working hours do not have a significant effect on Purun Al-Firdaus woven craft craftsmen. From the results of the regression carried out, an adjusted R square value of 0.454 was obtained, which means that the factors that influence the income of Purun Al-Firdaus woven craft craftsmen are 45.4% while the remaining 54.6% is explained by other variables.